Fetal and early neonatal interleukin-6 response. Issue 1 (November 2015) - Chiesa, Claudio; Pacifico, Lucia; Natale, Fabio; Hofer, Nora; Osborn, John F.; Resch, Bernhard
Highlights Fetal blood IL-6 may identify neonates at risk for adverse neonatal outcome. We review IL-6 reference intervals and dynamics during the early postnatal period. Stress, systemic injury and infection may affect IL-6 response in the early life. According to STARD, accuracy of IL-6 diagnostic studies for neonatal sepsis was sub-optimal. White matter injury may arise from postnatal infections through inflammatory IL-6 response.